2020
DOI: 10.1071/an19576
|View full text |Cite
|
Sign up to set email alerts
|

Free-range egg production: its implications for hen welfare

Abstract: Free-range laying hen housing systems are prevalent in Australia and perceived by consumers to provide greater opportunities for the expression of natural behaviour resulting in higher hen welfare. However, all housing systems have both benefits and risks and scientific evidence is needed on the welfare outcomes of free-range systems. In this review, the scientific literature is summarised from the past 10 years, from research conducted within Australia or internationally with brown laying-hen strains kept in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 59 publications
1
36
0
11
Order By: Relevance
“…This is similar to results in European countries [4,11], or Mexico [14]. Interestingly, the current scientific evidence seems to point out that free-range or cage-free production system impose a greater welfare risk (diseases, environmental harness) than those in cage and more intensified system [6,15]. There have been increasing reports of outbreaks of food transmitted diseases such as salmonellosis related to the consumption of eggs from free-range or cage-free systems [16,17].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This is similar to results in European countries [4,11], or Mexico [14]. Interestingly, the current scientific evidence seems to point out that free-range or cage-free production system impose a greater welfare risk (diseases, environmental harness) than those in cage and more intensified system [6,15]. There have been increasing reports of outbreaks of food transmitted diseases such as salmonellosis related to the consumption of eggs from free-range or cage-free systems [16,17].…”
Section: Discussionsupporting
confidence: 79%
“…Several studies have shown that public perception is that animals in free-range or cage-free egg production systems have better animal welfare than those in more intensive systems [4] [5]. Some studies have shown that cage-free or free-range hens may be subjected to poorer welfare and health [6][7][8][9]. Also, in an increasing global human population, cagefree or free-range production system seems unsustainable [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…However, even when the most favourable conditions are offered, chickens vary highly in the use of the range (Larsen et al 2017;Taylor et al 2017aTaylor et al , 2017bCampbell et al 2019a). Different ranging behaviour patterns are linked to different welfare consequences, either positive or negative, and need to be further understood (Bari et al 2020a(Bari et al , 2020bCampbell et al 2020a). The second welfare issue covered in this review is the feather pecking and cannibalism in laying hens, two of the most prevalent behavioural problems in laying hen flocks worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Consumers believe that fresh air and outdoor access for birds in the freerange system improve hen welfare (3). However, laying hens demonstrate marked individual dissimilarities in range use when provided with outdoor access, which may result in individual differences in welfare (8). Outdoor access and time spent ranging, a higher proportion of hens ranging, or distance of ranging by free-range hens may result in some welfare benefits to the birds.…”
Section: Introductionmentioning
confidence: 99%